Penerapan Teknologi Sidik Jari dalam Sistem Hukum: Tinjauan terhadap Prinsip – Prinsip Pembuktian - Lukman Hakim Harahap; Daiyatul Mardiah; Dinda Sherin Al Asya Sinaga; Raihan Ryanta Akbar; Sri Anggini Lubis (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The application of fingerprint technology in the legal system has brought significant changes to the evidentiary process. This technology enables the identification of individuals with high accuracy, which is an important element in law enforcement and dispute resolution. This study explores how fingerprint technology is applied in the Indonesian legal context, reviews relevant evidentiary principles, and analyzes the implications of its use in various legal cases. This research is descriptive analytical, meaning that this research aims to describe certain circumstances or situations of the objects or events being studied without intending to draw conclusions that can be applied generally. The approach used in this research is the normative juridical method. The results show that, although fingerprint technology makes a significant contribution to the effectiveness of evidentiary systems, fingerprint technology has long been used in the legal system as a tool for individual identification. Fingerprints, with their unique characteristics in each person, provide a guarantee of highly accurate identification. This technology is not only used in crime but also in various aspects of government and public services, such as population registration and securing access. The application of fingerprint technology in a modern legal context is becoming increasingly relevant with advances in digital technology that enable fast and efficient data processing. There are challenges related to privacy, data reliability and the integrity of legal processes. This research also proposes recommendations to increase the integration of fingerprint technology in the legal system in accordance with the principles of justice and human rights.